Thermoeconomic and optimization analyses of direct oxy-combustion supercritical carbon dioxide power cycles with dry and wet cooling - Ahmad K. Sleiti (14778229) (2021)
Oxy-combustion supercritical CO2 power cycles have the advantages of high-energy efficiency and near-zero pollutant emissions. Thus, these cycles are considered as an efficient way to reduce CO2 emissions while maintaining economic growth. The major drawbacks of this technology include the lack of validated levelized cost of electricity (LCOE) studies; lower turbine inlet temperatures studies to accommodate the integration of various energy sources; solutions for the thermodynamic imbalance of the regenerator; and investigating the dry- versus the wet-cooling methods. These drawbacks are addressed in this paper by presenting comprehensive thermoeconomic and optimization analyses for three direct oxy-fuel sCO2 power cycles in wet and dry-cooling conditions. The first cycle M1 is a direct oxy-fuel sCO2 power cycle without preheater, the second cycle M2 integrates a preheater in parallel with the low-temperature recuperator of M1 while the third cycle M3 integrates a preheater in parallel with the high and low-temperature recuperators of M1. Results show that the integration of the preheater improves the thermal efficiency of M2 by 5.81% (wet), and 3.27% (dry), and of M3 by 13.27% (wet), and 6.58% (dry). The LCOE of M1 (without preheater) is higher than that of M2 by 10.8% (wet), and 5.7% (dry), and of M3 by 19.1% (wet), and 11.4% (dry). A minimum LCOE of 4.667¢/kWhe is obtained for M3 (wet) and of 6.139¢/kWhe for M3 (dry). At higher waste heat source temperature of 700 °C, the overall efficiency is improved by an average of 11% and the LCOE is reduced by 1.43 ¢/kWhe. Other Information Published in: Energy Conversion and Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.enconman.2021.114607